POLICIES AND PROBLEMS IN FULFILLING THE RIGHTS OF CHILDREN WITH DISABILITIES IN INDONESIA (International Conference of Postgraduate Students and Academics in Syariah and Law, 2023)
Procedural law courses are important components in legal education in all law schools in Malaysia. The courses include Civil Procedure, Criminal Procedure, Evidence as well as a more specific courses such as Bankruptcy and Winding-up. These are taught as compulsory courses in upper years in which students have already completed substantive areas of law. In law schools that include Syariah law (Islamic law) as part of their curriculum, Syariah procedural courses both for criminal and civil proceedings are also taught. Similar to many other professional courses, teaching and learning professional skills require special approach different from traditional approach of lecture and …